1993
DOI: 10.1073/pnas.90.23.11132
|View full text |Cite
|
Sign up to set email alerts
|

A fertility region on the Y chromosome of Drosophila melanogaster encodes a dynein microtubule motor.

Abstract: A clone encoding a portion of the highly conserved ATP-binding domain of a dynein heavy-chain poly-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 35 publications
1
75
0
4
Order By: Relevance
“…Six of the dynein transcripts are abundant in testes, consistent with previous biochemical and genetic data that have shown that multiple dynein heavy chain polypeptides participate in axonemal motility (reviewed in Witman, 1992). One of the dynein genes that is expressed in testes, DhcYh3, is located on the Y chromosome within kl-5, a region that is required for male fertility (Brosseau, 1960;Hardy et al, 1981;Goldstein et al, 1982;Gepner and Hays, 1993). Another dynein gene identified in this study, Dhc64C, was previously recovered using expression cloning methods.…”
Section: Expression Of Drosophila Dynein Genessupporting
confidence: 81%
See 3 more Smart Citations
“…Six of the dynein transcripts are abundant in testes, consistent with previous biochemical and genetic data that have shown that multiple dynein heavy chain polypeptides participate in axonemal motility (reviewed in Witman, 1992). One of the dynein genes that is expressed in testes, DhcYh3, is located on the Y chromosome within kl-5, a region that is required for male fertility (Brosseau, 1960;Hardy et al, 1981;Goldstein et al, 1982;Gepner and Hays, 1993). Another dynein gene identified in this study, Dhc64C, was previously recovered using expression cloning methods.…”
Section: Expression Of Drosophila Dynein Genessupporting
confidence: 81%
“…However, the ability of the RT-PCR strategy to amplify and to assay the presence or absence of a specific dynein sequence is supported by the DhcYh3 observations. We have shown that DhcYh3 is located on the Y chromosome (Figure 3, see also Gepner and Hays, 1993) and therefore transcripts derived from this gene should only be present in males. As shown in Figure 5A, the DhcYh3 probe detects a product only in the RT-PCR reactions that used adult male RNA as the starting template.…”
Section: Expression Of Drosophila Dynein Genesmentioning
confidence: 87%
See 2 more Smart Citations
“…The Y chromosome is required for male fertility in most Drosophila species (Ashburner et al, 2005) even though it does not contain a male-determining gene. Instead, most if not all of the~14 protein-coding genes present on the Y chromosomes of Drosophila melanogaster, D. simulans and other closely related species have male-specific functions and are exclusively expressed in the testis (Gepner and Hays, 1993;Carvalho et al, 2000;Carvalho et al, 2001;Vibranovski et al, 2008). Nevertheless, a suite of studies have shown that genetic variation present on the Y of Drosophila underlie phenotypic variation in male fitness (Chippindale and Rice, 2001;Yee et al, 2015), sex ratio distortion (Carvalho et al, 1997;Montchamp-Moreau et al, 2001;Branco et al, 2013a, b), tolerance to temperature extremes (Rohmer et al, 2004;David et al, 2005), behavior (Stoltenberg and Hirsch, 1997;Huttunen and Aspi, 2003), gene expression (Lemos et al, 2008;Sackton et al, 2011;Branco et al, 2013a, b) and chromatin states in somatic tissues .…”
Section: Introductionmentioning
confidence: 99%